The influence of foreign and local cultures on traditional mosques in Indonesia case study: Banten Great Mosque Complex, Banten Province, West Java / Tessa Eka Darmayanti and Azizi Bahauddin - Darmayanti, Tessa Eka; Bahauddin, Azizi (Division of Research and Industry Linkages, UiTM Melaka, 2014)
This paper aims to investigate the influence of foreign and ocal culture infuence on the architecture and socio- cultural activities in the iconic Banten Great Mosque Complex. Indonesia has a strategic location, enabling it to become the 'melting pot' of various cultural development. This paper gives an alternative for the Banten Great Mosque research, as the focus is on three areas inside the complex, the main building of the Great Mosque as a religious space, the Tiyamah buildings where gatherings are held as a social space and the cemetery area with royal graves as an embodiment of the cultural tradition. This study applied the qualitative method with cultural studies and exploratory data approaches. This research is very important in the documentation of lslamic architecture and the cultural identity of Indonesia, which will then convey the historical knowledge to other countries, especially those that are connected historically and geographically.